2017
DOI: 10.1186/s12885-017-3474-3
|View full text |Cite
|
Sign up to set email alerts
|

Elevated serum CEA levels are associated with the explosive progression of lung adenocarcinoma harboring EGFR mutations

Abstract: BackgroundSerum carcinoembryonic antigen (CEA) levels are a predictor of epidermal growth factor receptor tyrosine kinase inhibitor (EGFR-TKI) efficacy and are associated with epidermal growth factor receptor (EGFR) gene mutations. However, the clinical significance of plasma CEA level changes during different cycles of target therapy is unknown for lung adenocarcinoma patients with sensitizing EGFR mutations.MethodsIn total, 155 patients with lung adenocarcinoma were enrolled in this retrospective study betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 42 publications
2
28
0
Order By: Relevance
“…Several recent studies have assessed their value for predicting EGFR mutation status and the therapeutic effects of TKIs. The serum CEA level in Chinese patients is not only positively associated with EGFR mutation, but also negatively associated with the efficacy of TKI therapy . Although data on Chinese patients is lacking, studies performed in other Asian countries have shown that serum Cyfra 21‐1 level was associated with EGFR mutation and tumor response to TKIs .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several recent studies have assessed their value for predicting EGFR mutation status and the therapeutic effects of TKIs. The serum CEA level in Chinese patients is not only positively associated with EGFR mutation, but also negatively associated with the efficacy of TKI therapy . Although data on Chinese patients is lacking, studies performed in other Asian countries have shown that serum Cyfra 21‐1 level was associated with EGFR mutation and tumor response to TKIs .…”
Section: Discussionmentioning
confidence: 99%
“…The serum CEA level in Chinese patients is not only positively associated with EGFR mutation, but also negatively associated with the efficacy of TKI therapy. 24,25 Although data on Chinese patients is lacking, studies performed in other Asian countries have shown that serum Cyfra 21-1 level was associated with EGFR mutation and tumor response to TKIs. 26,27 Our study indicated that patients with low Cyfra 21-1 (< 3.3 ng/mL) were more likely to harbor del19 or L858R mutations.…”
Section: Discussionmentioning
confidence: 99%
“…CEA was first described in 1965 by Gold and Freedman as an antigen present in gastrointestinal carcinoma cells [14,21]. A number of researches demonstrated the prognostic value of preoperative CEA levels as a classical marker for LUAD [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…CEA was first described in 1965 by Gold and Freedman as an antigen present in gastrointestinal carcinoma cells [14,19]. A number of researches demonstrated the prognostic value of the preoperative CEA level, as a classical marker for LUAD [20,21].…”
Section: Discussionmentioning
confidence: 99%